THE USE OF YOUTUBE-BASED LEARNING ANIMATION STORYTELLING VIDEOS TO IMPROVE SPEAKING OF SEVENTH GRADE MIDDLE SCHOOL STUDENTS - Ariandi, Sopian; Usuluddin; Fikni, Zahratul; Maysuroh, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Developing oral communication in EFL contexts is frequently challenged by students’ low speaking proficiency. This pre-experimental quantitative study investigated the extent to which YouTube-based learning animation storytelling videos improve the speaking skills of 30 seventh-grade students (Class VII A) at SMPN 1 Suralaga. Data were collected through oral assessments administered during pre-test and post-test phases, utilizing a rubric that evaluated pronunciation, vocabulary, grammar, and fluency. Results revealed a highly significant improvement in speaking performance, with the mean score surging from 5.83 in the pre-test to 10.33 in the post-test. A paired samples t-test confirmed this structural shift with a massive effect size While all assessed aspects improved, pronunciation and vocabulary exhibited the largest gains. Conclusively, integrating authentic multimodal storytelling media successfully elevates the overall classroom performance standard, bridges linguistic gaps, and cultivates students' speaking confidence.